Construções geométricas elementares na palma da mão - Lima, Américo José de (2021)
Cell phones in the classroom have been the focus of debates among experts and even laws have been proposed with the aim of prohibiting their use in this environment. So, why propose the use of GeoGebra on cell phone in teaching/learning Flat Euclidean Geometry? Particularly, was rarely used technological resources such as computers and software to teach Mathematics classes. I heard about GeoGebra but had no curiosity or interest in knowing about it. However, it only came to my attention during PROFMAT's Geometry classes in 2019. Then, in 2020, in the course Completion Work discipline, a research was proposed for the analysis of dissertations in the PROFMAT dissertation bank in order to observe the structure and organization according to ABNT norms. Nevertheless, I could observe that there were many works aimed at teaching Mathematics using GeoGebra on the computer. But not all schools are equipped with computer labs, or when they are, there are many bureaucracies that end up making it difficult for teachers to use them. Therefore, in light of this reality, we present in this work the use of GeoGebra software on cell phones as a tool to aid in teaching/learning Flat Euclidean Geometry, considering that mobile phones are a technology that is part of the daily lives of students and after installed it can be used offline at school (classroom), at home, that is, wherever you are, overcoming difficulties and barriers encountered. Finally, we propose the use of GeoGebra on cell phones to carry out elementary geometric constructions, enabling more dynamic and attractive classes to improve student performance and learning. We leave it as a suggestion for the teacher to start with a workshop class to help students install the software and recognize the tools contained in the Tool Window, thus facilitating their work with students during classes.